Oxidation of Aromatic Anils in Aniline Moiety by meta-Chloroperbenzoic Acid in Aqueous Acitic Medium - Venkatesh, R.; Karunakaran, K. (Asian Journal of Chemistry, 2015)
The kinetics of oxidation of aromatic anils in aniline moiety by meta-chloroperbenzoic acid (m-CPBA) has been studied in aqueous acitic medium. The order of reaction was found to be second order with respect to aromatic anil and first order with respect to m-chloroperbenzoic acid. The increase of [H+] in this oxidation retards the rate of reaction. The effects of substituents on the oxidation rate were studied with 3 meta- and 5 para- substituted anils at five different temperatures. Thermodynamic parameters for the oxidation have been determined and discussed. meta-Chloroperbenzoic acid oxidation with substituted anils fulfills the isokinetic relationship and Exner relationship but not to any of the linear free energy relationships. The deviation of Hammett plot was noted and a concave downward curve was obtained for the anils with substituents in aniline moiety.